Characterization of Reservoir Rocks of X Gas Field, Surma Basin, Bangladesh - Afroza Parvin; Md Jamilur Rahman; Abdus Samad; A.S.M. Woobaidullah (Geological Agency, 2021)
DOI:10.17014/ijog.8.3.417-426This paper deals with the rock physical analysis of primary reservoir rocks in the X gas field, which includes identifying the transition zone between mechanical and chemical compaction zones and the amount of cement in the reservoir rock. The analysis is performed by plotting different log data (Gamma-ray, density, neutron porosity, and sonic log) against depth, constructing the cross plot, and plotting of sonic and porosity logs with cement model. The transition zone, which is the boundary between mechanical and chemical compactions, indicates a sharp increase in density and a decrease in porosity with no lithological change at 2,576 m depth (Well-2). Among three gas sands, the upper gas sand and upper part of the middle gas sand are located within the mechanical compaction zone. The lower parts of the middle gas sand and lower gas sand are within the chemical compaction zone. Cement model analysis showed that the upper gas sand and upper part of the middle gas are composed of unconsolidated sand. In contrast, the lower part of middle gas sand and lower gas sand comprise of consolidated sand, having almost 2% contact cement.